Evaluating short-term musculoskeletal pain changes in desk-based workers receiving a workplace sitting-reduction intervention - Brakenridge, C.; Chong, Y.; Winkler, E.; Hadgraft, N.; Fjeldsoe, B.; Johnston, V.; Straker, Leon; Healy, Genevieve; Clark, B. (Molecular Diversity Preservation International (MDPI), 2018)
This paper explores changes in musculoskeletal pain among desk-based workers over three months of a workplace-delivered, sitting-reduction intervention. Participants (n = 153, 46% female; mean ± SD aged 38.9 ± 8.0 years) were cluster-randomized (n = 18 work teams) to receive an organizational change intervention, with or without an activity tracker. A modified Nordic Musculoskeletal Questionnaire assessed pain intensity (0–9; none–worst possible) in the neck, upper and lower back, upper and lower extremities, and in total. The activPAL3 (7 days, 24 h/day protocol) measured sitting and prolonged sitting in =30 min bouts at work. Mixed models adjusting for cluster and intervention arm examined changes in pain (n = 104), and their associations with reductions in sitting and prolonged sitting (h/10 h at work) (n = 90). Changes in pain were nonsignificant (p = 0.05) and small for total pain (-0.06 [95% CI: -0.27, 0.16]) and for each body area (-0.26 [-0.66, 0.15] for upper back to 0.09 [-0.39, 0.56] for lower back). Sitting reduction was associated with reduced lower back pain (-0.84 [-1.44, -0.25] per hour, p = 0.005); other effects were small and non-significant. No substantial average changes in pain were seen; some improvement in lower back pain might be expected with larger sitting reductions. Larger samples and diverse interventions are required for more definitive evidence.